2010
DOI: 10.1002/jso.21513
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the drug resistance‐associated protein metallothionein does not correlate with response of sarcomas to isolated limb perfusion treatment

Abstract: Background and Objectives: Hyperthermic isolated limb perfusion with TNF-a and melphalan (HILP-TM) achieves high response rates in sarcomas. Melphalan resistance was previously reported to be associated with overexpression of metallothioneins (MTs). Objective of this study was to investigate the influence of MT expression on tumor responses in HILP-TM-treated soft tissue (STSs) and bone sarcomas (BS). Methods: In primary biopsies of 41 HILP-TM-treated sarcomas (37 STSs and 4 BS), MT expression was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…MT was detected both by immunohistochemistry and by real time (RT) PCR. 66,205 Similar results were described by Hishikawa and co-workers in oesophageal cancer. They found more frequent 5-year survival of patients suffering from squamous cell oesophageal cancer treated with cisplatin in MT negative than MT positive tumours.…”
Section: Clinical Relevance Of Mtsupporting
confidence: 83%
“…MT was detected both by immunohistochemistry and by real time (RT) PCR. 66,205 Similar results were described by Hishikawa and co-workers in oesophageal cancer. They found more frequent 5-year survival of patients suffering from squamous cell oesophageal cancer treated with cisplatin in MT negative than MT positive tumours.…”
Section: Clinical Relevance Of Mtsupporting
confidence: 83%
“…Most of these have focused on adults [6,18,29–33] and far fewer on children [34–37]. Studies in adults have shown that cellular MT could serve as prognostic markers in some tumours [17,3843]. Relationships have been described between MT and p53 status [1], increased tumour grade [44,45] and metastases development [1,46].…”
Section: Discussionmentioning
confidence: 99%
“…to the MTs level have been published [214]. On the other hand in some other studies devoted to colorectal and bladder cancer and others, no significant correlation between MTs expression and prognosis was observed [215][216][217]. The relationship between MTs and cancer has been discussed in details recently in review by Eckschlager et al [218].…”
Section: Metallothionein and Tumor Diseasementioning
confidence: 99%